Genetic stability of melon (Cucumis melo L. cv. Meloni) based on inter-simple sequence repeat and phenotypic characteristics - ADIB FAKHRUDDIN YUSUF; WIKO ARIF WIBOWO; BUDI SETIADI DARYONO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Yusuf AF, Wibowo WA, Daryono BS. 2022. Genetic stability of melon (Cucumis melo L. cv. Meloni) based on inter-simple sequence repeat and phenotypic characteristics. Biodiversitas 23: 3042-3049.A new cultivar must have a character that follows the official criteria of distinctness, uniformity, and stability (DUS) as required for the grant of Plant Breeder Rights and official cultivar registration. Meloni is a new cultivar resulting from plant breeding by the Genetics and Breeding Laboratory of the Faculty of Biology, Universitas Gadjah Mada. Legality is needed in the form of plant variety protection (PVT)to protect the intellectual rights of researchers. Therefore, this study aims to identify morphological characters according to official criteria and validate molecular feelings by using molecular markers Inter-Simple Sequence Repeat. The results of morphological characterization showed that the distinctive character of the Meloni cultivar lies in the oval shape of the fruit, the skin of the fruit is creamy with a smooth texture without the net, and the flesh of the fruit is orange with a sweet taste. The differences in morphological characters of the Meloni cultivar cultivated at two locations differ in fruit weight, flesh thickness, fruit shelf life, and harvest age. Molecular identification resulted in a low similarity in the phenetic relationship, namely 35% against Sonya cultivars and 51% against Kirani and Kinanti cultivars. The Meloni cultivar's stability and uniformity analysis between the two locations (Bandung, West Java, and Sleman, Yogyakarta) yielded 76%. The difference in cultivation locations did not affect the level of stability and genetic uniformity of the Meloni cultivar.